EFFECTIVENESS OF PHYSIOTHERAPY TREATMENT IN PATIENTS WITH INTELLECTUAL DISABILITY AND CONDUCT DISORDER (Cuestiones de Fisioterapia, 2016)
Introduction: people with intellectual disability and behavior disorder usually have disorders of gait, balance and activities of daily living. Objectives: a. To verify if these patients improve gait, balance and activities of daily living after a physiotherapeutic treatment, using as a measure Tinetti scale and the Barthel index; and b. To determine whether the initial state, age, use of sedative medication, number of sessions, degree of disability and sex, are interaction variables. Material and method: uncontrolled trial; sample: 14 patients of Residencia San Sebastián in Cantillana (Sevilla); inclusion criteria: diagnosed with intellectual disability and behavior disorder, being admitted to Residencia San Sebastian and present walking, balance and activities of daily living difficulties, aspects that were evaluated before and after treatment. Data was analyzed using Medcalf V11.3.0.0. Results: a significant improvement was observed after treatment of physiotherapy: Tinetti (p = 0.0001) Barthel (p = 0.00021). In 78.51% of the final scores of the Tinetti scale and in 91.42% of the Barthel index, the initial state, the age and the number of sessions influenced, being significant the initial state. Conclusions: physiotherapy intervention significantly improves the disorders of gait, balance and activities of daily living. A better initial state influences the final score. The other studied interaction variables did not in-fluence significantly the results of the study.